2014
DOI: 10.1021/pr5006668
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomics Approach for Identifying Glycobiomarker Candidate Molecules for Tissue Type Classification of Non-small Cell Lung Carcinoma

Abstract: Histopathological classification of lung cancer has important implications in the application of clinical practice guidelines and the prediction of patient prognosis. Thus, we focused on discovering glycobiomarker candidates to classify the types of lung cancer tissue. First, we performed lectin microarray analysis of lung cancer tissue specimens and cell lines and identified Aleuria aurantia lectin (AAL), Hippeastrum hybrid lectin (HHL), and Concanavalia ensiformis agglutinin (ConA) as lectin probes specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…The glycan structures on these proteins, however, have not been elucidated. The neuroendocrine marker NCAM1 was detected only in SCLC cell lines [42]. Upregulation of APLP1 has been reported in neuroendocrine tumors [43].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The glycan structures on these proteins, however, have not been elucidated. The neuroendocrine marker NCAM1 was detected only in SCLC cell lines [42]. Upregulation of APLP1 has been reported in neuroendocrine tumors [43].…”
Section: Resultsmentioning
confidence: 93%
“…Thus, these sulfated glycoproteins may be relatively abundant in the serum-free culture medium of H2171 cells. Recently, Hirao et al identified GOLM1 and IGFBPL1 in the culture media from SCLC and NSCLC cells using lectin-based glycoproteomic analysis [42]. The glycan structures on these proteins, however, have not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…A lectin-based microarray analysis discriminated between healthy patients and patients with colorectal cancer due to the higher degree a α2,6-sialylation and the higher content in high mannose N -glycans in serum α2-macroglobulin [125]. Glycosylation profiling of fibronectin performed with a lectin-microarray, showed that PNA distinguishes between two distinct types of non-small cell lung carcinomas, lung adenocarcinoma and large cell lung carcinoma [126]. In a lectin-microarray analysis including the T/Tn-specific lectins ACA ( Amaranthus caudatus ), ACG ( Agrocybe cylindracea ), BPL ( Bauhinia purpurea ), and SNA ( Sambucus nigra ), a decreased lectin-binding activity was observed for Tn antigen from formalin-fixed human choriocarcinoma tissues [24].…”
Section: Tn/t-specific Lectins For Cancer Diagnosis/prognosismentioning
confidence: 99%
“…For instance, lung cancer can be classified into small cell carcinoma, adenocarcinoma, squamous cell carcinoma and large cell carcinoma, while ovarian cancer is classified into clear cell carcinoma, mucinous adenocarcinoma, serous adenocarcinoma and endometrioid adenocarcinoma. If the histological types of cancer in the same organ are different, glycan structures and probing lectins are largely different and distinctive [14,46]. Therefore, a collaborative study with experienced clinical doctors and pathologists is essential.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…For instance, structures of glycans are different between small cell lung carcinoma and non-small-cell lung carcinoma [14], or among hepatoma, hepatocellular carcinoma and intrahepatic bile duct carcinoma [15]. Glycans are also expected to be useful as specific markers in the research and production of stem cells and induced pluripotent stem cells [16].…”
mentioning
confidence: 99%